Rheological, thermal, and electrical characterization polyamide/polypropylene blend composites containing hybrid filler: Boron nitride and reduced graphene oxide. (5th April 2021) - Seyed Esfahani, Seyed Armin; Ghahramani, Nikoo; Mehranpour, Milad; Nazockdast, Hossein
Abstract: In this study, the microstructural development and its effect on the thermal conductivity of polyamide6 (PA6)/polypropylene (PP) blends containing boron nitride (BN) and reduced graphene oxide (rGo) as hybrid fillers were investigated. Blend samples were prepared using the masterbatch method to localize BN and rGo in the matrix phase (PA6). Dynamic rheological results were consistent with selective localization of the fillers in PA6 as evidenced by nonterminal behavior (3D network) PP/PA‐BN at low frequencies. Compared with the case where the matrix phase (PA6) was only filled with BN particles, thermal conductivity measurements showed that replacing 10% and 15% BN particles with rGo nanoparticles yielded higher thermal conductivity. The hybrid fillers had a synergetic effect on the heat conductive network, forming a more efficient percolating network of BN and rGo in the matrix phase (PA6). A comparison between the BN‐filled PA6 blend and the BN‐rGo‐filled PA6 blend revealed higher thermal conductivity in the PP/PA6‐BN‐rGo sample with co‐continuous morphology than in the PP/PA6‐BN sample with matrix‐disperse morphology. Abstract :